The Influence Of Leadership Style, Work Discipline, And Work Motivation On The Work Morale Of Iia Curup Prison Employees - Jalil Majid; Ratnawili Ratnawili (Penerbit Jurnal Indonesia, 2024)
This research was conducted on IIA Cuirup Rejang Lebong Prison Employees with the problem formulation: What is the Influence of Leadership Style, Work Discipline and Work Motivation on Employee Work Morale among IIA Cuirup Rejang Lebong Prison Employees? and the aim of this research is to find out whether Leadership Style, Work Discipline, and Work Motivation affect employee morale among employees at IIA Cuirup Rejang Lebong Prison. The population in this study are employees at IIA Cuirup Rejang Lebong Prison. totaling 85 respondents. The sampling technique used accidental sampling based on predetermined criteria, totaling 85 respondents. The processed data was analyzed using the SPSS 26 formula. Based on the results of research and analysis of the influence of the Leadership Style (X1) and Work Discipline (X2) variables on Work Morale among Kleas IIA Curup Rejang Lebong Prison Employees. The following conclusion can be drawn: Leadership Style (X1) has a positive effect on Work Morale (Y) of Employees at the Kleas IIA Curup Rejang Lebong Prison. This is proven by hypothesis testing with the t-test, obtained tcount > ttable (3,286,> 1,989) Work Discipline (X2) has a positive effect on Work Morale (Y) of Employees at the Kleas IIA Curup Rejang Lebong Prison. This is proven by hypothesis testing with the t-test, obtained tcount > ttable (4,612> 1.989) Work Motivation (X2) has a positive effect on Work Morale ( Y) Employees at the Kleas IIA Curup Rejang Lebong Prison. This is proven by hypothesis testing with the t-test, obtained tcount > ttable (2,879>1.989).Leadership Style (X1), Work Discipline (X2), and Work Motivation (X3) have an effect on Work Morale (Y) Employee. This can be seen from joint hypothesis testing (Simultaneous) Fcount > Ftable (78.007 > 2.722). This is proven by the correlation analysis R = 0.862 or (84.8%) and is almost close to 1. And the coefficient of determination is R2 = 0.743 or around 71.9% while 28.1% is the contribution of other variables not studied.